Witnesses stumbling down memory lane: The effects of alcohol intoxication, retention interval, and repeated interviewing. Issue 4 (21st April 2017) - Hagsand, Angelica V.; Roos af Hjelmsäter, Emma; Granhag, Pär Anders; Fahlke, Claudia; Söderpalm Gordh, Anna
ABSTRACT: Intoxicated eyewitnesses are often discredited by investigators and in court, but few studies have examined how alcohol affects witnesses' memory. The primary aim of the present study was to examine how intoxication (alcohol vs. control), retention interval (immediate vs. one week delay), and number of interviews (one vs. two interviews) affect witnesses' memory. The participants ( N = 99) were randomly assigned to consume either orange juice or alcohol mixed with orange juice, and they all witnessed a filmed mock crime afterwards. The recall took place either (a) immediately and after a one week delay or (b) after a one week delay only. No main effect of alcohol was found on the quantity or quality of the witnesses' statements. Both intoxicated and sober witnesses recalled more details, and were more accurate, during immediate compared to delayed recall. For witnesses interviewed twice, an average of 30% new details were provided in the second compared to the first interview, and these were highly accurate. In sum, contrary to what one can expect, intoxicated witnesses with a low to moderate blood alcohol concentration (below 0.10%) were reliable witnesses.